Cultural Adaptation in Film Subtitles: A Study of Brazilian Films for Hispanic Audiences - Ana Luisa Ferreira (Journal of Linguistics and Communication Studies, 2024)
This paper explores the challenges and strategies involved in the cultural adaptation of Brazilian films subtitled for Hispanic audiences. Given the linguistic and cultural differences between Brazil and the Hispanic world, translating culturally specific elements such as idioms, humor, and social norms presents unique difficulties. Through an examination of case studies of Brazilian films like Cidade de Deus and Tropa de Elite, the paper highlights various subtitling techniques, including localization, contextualization, and dynamic equivalence, which are used to make these films accessible to Hispanic viewers. The analysis also considers how effective cultural adaptation impacts audience reception, influencing both their understanding and emotional engagement. Finally, the paper discusses the broader implications of cultural adaptation in film subtitling, particularly in fostering cross-cultural comprehension and enhancing the viewing experience.